Understanding sexual violence and factors related to police outcomes - Davies, Kari; Spence, Ruth; Cummings, Emma; Cross, Maria; Horvath, Miranda A. H. (Frontiers in Psychology, 2022)
In the year ending March 2020, an estimated 773,000 people in England and Wales were sexually assaulted. These types of crimes have lasting effects on victims’ mental health, including depression, anxiety, and post-traumatic stress disorder. There is a large body of literature which identifies several factors associated with the likelihood of the victim reporting a sexual assault to the police, and these differences may be due to rape myth stereotypes which perpetuate the belief that rape is only “real” under certain conditions. Less is known, however, about the effect these rape myths and stereotypes have on the investigation process itself and the subsequent police outcomes assigned to sex offences. This study aimed to address this gap, providing a profile of all RASSO (rape and serious sexual offences) committed over a 3-year period in one English police force, the police outcomes of these offences, and whether any offences, suspect, or victim variables were associated with different outcomes, in particular the decision to charge or cases where victims decline to prosecute. In line with previous research, the majority of victims were female while the majority of suspects were male, and the most frequent victim–suspect relationship was acquaintance, followed by partner/ex-partner. Charge outcomes were more likely in SSOs and less in rape offences, more likely with stranger offences and less likely than offences committed by partners/ex-partners and relatives, and some non-white suspects were more likely to be charged than suspects of other ethnicities, including white suspects. Victim attrition was more likely in cases where the suspect was a partner or ex-partner and least likely where the suspect was a stranger, more likely in SSOs than in rape cases, and more likely when the victim ethnicity was “other”. Law enforcement should be aware of the potential biases, both relating to rape myths and stereotypes and to the biased treatment of victims and suspects based on demographic characteristics, and work to eliminate these to ensure a fairer and more effective RASSO investigative process.